Implementasi Media Rute Perjalanan Berbasis Project Based Learning (PjBL) terhadap Kemandirian Belajar dan Kemampuan Berpikir Kritis Siswa Kelas IV SD Negeri Wonoplumbon 02 Semarang - Karunia Safitri; Panca Dewi Purwati (Mathematics Education Study Program, 2025)
Learning activities in the fourth grade of SD Negeri Wonoplumbon 02 initially showed low independence and critical thinking because students tended to remain passive during lessons. This study aimed to describe the implementation of the travel route media through Project Based Learning and to examine its effectiveness in improving students’ learning independence and critical thinking skills. A mixed-methods approach was used through observation, interviews, and documentation. Students worked on a project to draw their travel route from home to school by observing their surroundings, determining directions, and presenting the final product. The results indicate that the project succeeded in increasing students’ participation, responsibility, curiosity, and confidence in expressing ideas. Learning achievement reached 80.29, with 14 students meeting the minimum mastery standard. It can be concluded that travel route media based on Project Based Learning is effective in improving learning independence and critical thinking.